Cross-sectional analysis of caesarean sections according to the Robson 10-group classification system in Somalia - Adil Barut; Umut Erkok; Hiba Bashir Hassan (BMJ Open)
Background Caesarean section (CS) is an important indicator of access to and quality of maternal health services. The WHO recommends the Robson 10-group classification system as a global standard for assessing, monitoring and comparing CS rates at all levels. Identification of the Robson groups that contribute the most to the overall CS is important to determine possible modifiable factors in our attempts to reduce the CS rate. This study was designed to analyse CS deliveries performed in a tertiary referral centre in Somalia according to the Robson 10-group classification system.Design This retrospective study included data on consecutive mothers who had deliveries from 1 January 2022 to 1 July 2023.Methods Data were categorised according to the Robson classification. Each patient’s data was coded according to Robson’s specifications.Results A total of 3030 deliveries were analysed. Of these, 1156 (38.2 %) were CS. Among the five largest Robson groups, the highest absolute contribution to CSs was found in group 5, with 11.4% followed by group 10 with a corresponding contribution of 9.4%. In the next three largest Robson groups (groups 1, 3, 4), the absolute contributions were 3.9%, 3.4% and 3.3%, respectively. The total percentages of CSs among all deliveries (n=3030) and among all CSs (n=1156) in the five largest Robson groups were 31.3% and 82.2%, respectively.Conclusion Our analysis showed that the overall caesarean section rate was 38.2%, and those major contributors were Robson groups 5 and 10.